Resonance Marketing 5.0: The Voice Of Young Urban Consumers in the Integrated Marketing Communications Landscape - Siti Fatimah; Syahrial Shaddiq; Khuzaini, Khuzaini; Rico, Rico (Sean Institute, 2025)
Marketing communication strategies applied to young urban consumers from Generation Z need to respond to emotional expectations and social values more meaningfully. Using a qualitative approach, constructivism paradigm, and phenomenology method, this study explores the experiences of five informants who actively interact with brands through digital media. The findings reveal that the resonance of marketing communication is greatly influenced by emotional involvement, participation in brand narratives, and consistency of values between brand messages and actions. Marketing 5.0, which combines technology and human empathy, has proven effective when applied authentically through integrated communication. The informants responded positively to personalization and collaboration-based strategies, but showed a critical attitude towards the mismatch between social messages and actual practices. IMC that is able to convey cohesive messages across channels, and encourage two-way interactions, has a greater chance of building consumer trust and loyalty. The results of this study show that the success of brand communication in the digital era is not only determined by the sophistication of technology, but by the authenticity, consistency, and collaborative values felt by the audience. The implications of these findings underline the importance of developing marketing strategies that are sensitive to the social and emotional dynamics of Generation Z.